Experimental Determination Of The Boiling Point Of Tomato Paste - et. al., Musaeva Rano Xalikovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The boiling point is the main indicator of the concentration of tomato paste, which characterizes the state of equilibrium of systems at certain pressures in the apparatus; at constant pressure, the boiling point of the solution depends on its concentration. The boiling point of solutions can be determined according to Raoult's law. The boiling point of plant solutions and the vapor pressure of the solvent above it deviate from the regularities inherent in ideal solutions. Therefore, various empirical formulas have to be used for calculations. If the boiling point of the pure solvent tp is known, then the boiling point of the product can be expressed as